Broadband Internet and Political Participation - Evidence for Germany - Nina Czernich (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2011)
Previous studies found the introduction of the today well established media radio and television to affect political participation. This paper evaluates the effect of the relatively recent introduction of a new medium, broadband internet. OLS resultssuggest a positive association between DSL availability and voter participationacross German municipalities. However, the roll-out of DSL networks is not random. The paper exploits the fact that DSL availability depends on a unicipalitys distance to the nearest interconnection point to the existing voice-telephony network. Instrumental-variable results using this distance to predict DSL availability confirm the effect of DSL availability on voter participation.
Keywords: D72; L96; O33; 330; Broadband internet; political economics; media; voting behaviour; Breitbandkommunikation; Internet; Mediennutzung; Partizipation; Wahlverhalten; Deutschland